Do Fome Zero ao Bolsa Família: da emancipação ao assistencialismo? - Martins, Barby de Bittencourt (2011)
As the moment Luis Inácio da Silva has rise to power in Brasil, the country witnessed to a change in social policies. President Lula's government soon began to implement the Zero Hunger Programme (Programa Fome Zero), a series of initiatives aimed at eliminating hunger in Brasil. This programme contained huge proportions and represented the social flag against the poverty. By the way, with time the programme lost attention and the Family Grant Programme (Programa Bolsa Família) became the centre of attention for the government. Besides, critics started to indicate that Family Grant is not such emancipative programme as Zero Hunger seems to be. Therefore the need to comprehend those programmes and discover their forms arises as a question point. That will be transitioned from a emancipative programme to a welfare one?